2007
DOI: 10.4103/0019-5545.33254
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal pattern of psychiatry service utilization in a tertiary care hospital

Abstract: Background:Seasonal and monthly variations in utilization of psychiatric services have been inadequately studied in India.Aims:This study sought to determine the pattern of psychiatric services utilization by patients with four broad categories of diagnosis (mood disorders (F30-39): neurotic stress-related and somatoform disorders (F40-48), schizophrenia, schizotypal and delusional disorders (F20-29) and mental and behavioral disorders due to psychoactive substance use (F10-19) in different seasons and months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 9 publications
4
18
0
Order By: Relevance
“…A study in Israel found that psychiatric admissions for patients with schizophrenia were higher in the summer and that admission rates were correlated with the mean maximal monthly temperature (4). Similarly, a study from India reported higher psychiatric service use in summer and autumn, especially by patients with mood disorders, when temperatures were highest (11).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Israel found that psychiatric admissions for patients with schizophrenia were higher in the summer and that admission rates were correlated with the mean maximal monthly temperature (4). Similarly, a study from India reported higher psychiatric service use in summer and autumn, especially by patients with mood disorders, when temperatures were highest (11).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies performed previously examined one or two performance indicators in piecemeal such as bed utilisation indices, 12 BOR and ALS. 13 Although single indicator is easy to use but may lead to misleading results. 14 For example, high BOR may not necessarily indicate optimal utilisation of beds which signifies good performance, rather may indicate long term unnecessary hospitalisation of patient or poor nursing care, delayed diagnostic and therapeutic interventions or development of hospital acquired infections.…”
Section: Discussionmentioning
confidence: 99%
“…The number of psychiatric beds occupied during the study period exhibited a significant seasonal variation suggesting that short-term fluctuations in atmospheric activity may dictate some of the periodicities in psychiatric psychopathology. A study showed a relationship between seasonal visits in the summer and fall and the number of of patients with mood disorders, neurotic stress-related and somatoform disorders recorded (Singh et al, 2007). A review about seasonal affective disorder (SAD), described, thoroughly byboth retrospective and prospective studies, the actuality of seasonal variation in mood and that, in the general population, depressive symptoms peak in winter, and the most extreme form of this disposition, SAD, appears to be a relatively common disorder (Magnusson, 2000).…”
Section: Introductionmentioning
confidence: 99%